Distributed multimedia framework using cobra on java technology with microsoft access and IBM DB2 database - Ahmad Shukri Mohd Nor (Fakulti Sains dan Teknologi, 2011)
Over the last decade, multimedia computing has grown from a specialist field into a pervasive aspect of everyday computing systems. Methods of programming and handling of multimedia information have evolved considerably over this period. Particular challenges for multimedia computing come from the mobility of the modern computer users, where wide-ranging levels of connectivity require that applications adapt to remain effective.